Phytochemical analysis and Antibacterial Activity of Acetone Extract of Secang (Caesalpinia sappan L) - Juwitaningsih, Tita; Sri Adelia Sari; Iis Siti Jahro; Neneng Windayani (Tropical Biopharmaca Research Center, IPB University, 2021)
In North Sumatra, the stem of the secang (Caesalpinia Sappan L) has been used in traditional medicine. This study aimed to conduct phytochemical analysis of the acetone extract of C. sappan and determine its antibacterial potency. Phytochemical test using 1H-NMR spectroscopy method andantibacterial activity were carried out on six pathogenic bacteria, including paper disc diffusion tests, determination of the minimum inhibitory concentration (MIC) using the microdilution method, and minimum bactericidal concentration (MBC). Based on 1H-NMR spectroscopic data, the acetone stem extract of C. Sappan L contains flavonoids and terpenoids and has activity against all tested bacteria with an inhibition zone in the range of 6.20 ± 0.53 - 10.93 ± 2.55 mm, MIC 312 - 5000 µg / mL and MBC 625-> 5000 µg / mL. The acetone extract of C. sappan showed the best activity against S. aureus ATCC 25923 with a MIC of 312 µg / mL. C. sappan L is a potential source of new antibacterial compounds.